Comparison of Campylobacter jejuni Isolates Implicated in Guillain-Barré Syndrome and Strains That Cause Enteritis by a DNA Microarray - Leonard, Edward E. (American Society for Microbiology, 2004)
We asked whether Campylobacter jejuni isolated from patients with Guillain-Barré syndrome (GBS) differ from isolates isolated from patients with uncomplicated gastrointestinal infection using DNA microarray analysis. We found that specific GBS genes or regions were not identified, and microarray analysis confirmed significant genomic heterogeneity among the isolates.